Effect of new zirconia surface coatings on the surface properties and bonding strength of veneering zirconia substrate - Farhan, Firas Abdulameer; Sulaiman, Eshamsul; Kutty, Muralithran Govindan (Elsevier, 2018)
Zirconia ceramic dental restorations showed a low bond strength to veneering ceramic because of there is no inherent glass content along with a nonpolar covalent bond in its matrix. Two zirconia coatings by airbrush spraying were used as a new surface treatment on zirconia substrate to create surface roughness and improved bond strength to the veneering ceramic. Unsintered yttria stabilized zirconia (YSZ) powder was partially sintered at 1100 °C to produce powders with two particle sizes; A = 26.0 ± 0.3 μm and B = 47.0 ± 0.5 μm. Unsintered YSZ blocks were sectioned into 50 discs of 25 mm in diameter and 2.5 mm in thickness. The discs were divided according to the surface treatments into three groups; ten sintered YSZ discs were blasted by airborne particle abrasion (APA) with 50 μm aluminium oxide particles as control group; twenty unsintered YSZ discs were coated with a mixture of glaze ceramic and YSZ powders (M1), and twenty unsintered YSZ discs were coated with a mixture of ceramic liner and YSZ powders (M2). Based on the sizes of the YSZ powders, the coated groups subdivided into M1A, M1B, M2A and M2B. The surface area roughness (Sa), surface morphology, elemental composition, phase transition and shear bond strength test (SBS) were assessed. The collected data were analysed with one-way ANOVA and Tukey HSD test at (P < 0.05). The Sa results revealed significant differences among all groups (P < 0.000). The coated groups showed higher Sa and SBS values with a significant difference than APA. The M1B group exhibited higher values of Sa (10.33 μm) and SBS (37.54 MPa) with significant differences among the other tested groups. The zirconia specimens treated with new coatings significantly improved the shear bond strength to the veneering ceramic.